METHODOLOGICAL PRINCIPLES OF STUDYING THE PROBLEM PROFESSIONAL AND PEDAGOGICAL ACTIVITY IN THE SYSTEM HIGHER PEDAGOGICAL EDUCATION - І.О. Palshkova (Academy of Cognitive and Natural Sciences, 2003)
No abstract